2017
DOI: 10.1038/ncomms15227
|View full text |Cite
|
Sign up to set email alerts
|

Inferring personal economic status from social network location

Abstract: It is commonly believed that patterns of social ties affect individuals' economic status. Here we translate this concept into an operational definition at the network level, which allows us to infer the economic well-being of individuals through a measure of their location and influence in the social network. We analyse two large-scale sources: telecommunications and financial data of a whole country's population. Our results show that an individual's location, measured as the optimal collective influence to t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 28 publications
1
43
0
2
Order By: Relevance
“…There is enough evidence to justify the significant relationship between mobile phone usage and many socioeconomic factors such as demographic statistics and education levels (Frias-Martinez and Virseda, 2012). In particular, previous research showed that an individual's wealth can be predicted at high accuracy from features of personal social network retrieved from his/her mobile phone calls and SMS metadata (Luo et al, 2017). Therefore, mobile phone metadata provides an alternative to collecting localized and timely information and again, serves as a complement of the traditional methods such as household survey data and national censuses, often at a relatively lower data acquisition cost.…”
Section: Mobile Phone Calls and Sms Datamentioning
confidence: 99%
“…There is enough evidence to justify the significant relationship between mobile phone usage and many socioeconomic factors such as demographic statistics and education levels (Frias-Martinez and Virseda, 2012). In particular, previous research showed that an individual's wealth can be predicted at high accuracy from features of personal social network retrieved from his/her mobile phone calls and SMS metadata (Luo et al, 2017). Therefore, mobile phone metadata provides an alternative to collecting localized and timely information and again, serves as a complement of the traditional methods such as household survey data and national censuses, often at a relatively lower data acquisition cost.…”
Section: Mobile Phone Calls and Sms Datamentioning
confidence: 99%
“…There is a growing effort in the field to combine online behavioral data with census records, and expert annotated information to infer social attributes of users of online services. The predicted attributes range from easily assessable individual characteristics such as age [15], or occupation [11,[16][17][18], to more complex psychological and sociological traits like political affiliation [19], personality [20], or SES [11,21].…”
Section: Related Workmentioning
confidence: 99%
“…There is a growing effort in the field to combine online behavioral data with census records, and expert annotated information to infer social attributes of users of online services. The predicted attributes range from easily assessable individual characteristics such as age [18], or occupation [20], [22], [41], [42] to more complex psychological and sociological traits like political affiliation [46], personality [44], or SES [35], [42].…”
Section: Related Workmentioning
confidence: 99%